Jagannath Mahadev Temple - Ghosh, Ayan (2023)
Jagannath Mahadev Temple was founded around 1858 by a Bombay merchant, Lakshmidas Jagjivandas. The temple is noted for its mix of elements of past and present, such as use of asbestos shade over the sabhamandap, intricately carved wooden brackets and use of bathroom tiles in the garbagriha replicating the artwork of Raja Ravi Varma. The inner sanctum houses a stone lingam and is mounted with a Nagara style shikhara.